Dampak Fatherless terhadap Kenakalan Remaja - Vanesha Naifah Ntoma; Ati Kusmawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
There are many phenomena of juvenile delinquency that still often occur around. Among juvenile delinquents are brawls between schools, skipping school, using illegal drugs, drinking alcohol. The role of the family is needed in this case, especially the mothers of children who experience fatherlessness due to parental divorce. The place of research is SMA Negeri 4 South Tangerang, which is located at Komp. Pertamina, Jl. W.R. Supratman-South Tangerang. The implementation of this research was carried out within 2 months, starting from July 27, 2023 to September 12, 2023. This type of research is qualitative research, and uses methods in the form of interviews, observation, and documentation. The results of the study are knowing the impact of delinquency and efforts to prevent and handle juvenile delinquency such as guidance from parents and a supportive surrounding environment. Through the main role of the family in overcoming juvenile delinquency who experience fatherlessness can help these adolescents to rise, never give up and get motivation from the closest environment, namely the family. Can be caused by divorce, death of the father, separation due to problems in the marriage relationship, or separation due to physical or psychological health problems respectively. Suggestions for parents always accompany and guide the development of adolescents so as not to cause juvenile delinquency.